2017
DOI: 10.1097/acm.0000000000001940
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Institutional Longitudinal Faculty Development Program in Humanism Supports the Professional Development of Faculty Teachers

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Related, prior research has supported the positive effects of similar longitudinal, small‐group faculty development programs aimed at strengthening humanistic teaching and role modelling. A large study by Branch and colleagues found that many participants had progressed to more advanced stages of professional identity formation after completing the programme. Achieving professional identity formation has recently been touted as the new goal to measure competence, as values and attitudes of the professional become incorporated into the identity of the aspiring physician .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related, prior research has supported the positive effects of similar longitudinal, small‐group faculty development programs aimed at strengthening humanistic teaching and role modelling. A large study by Branch and colleagues found that many participants had progressed to more advanced stages of professional identity formation after completing the programme. Achieving professional identity formation has recently been touted as the new goal to measure competence, as values and attitudes of the professional become incorporated into the identity of the aspiring physician .…”
Section: Discussionmentioning
confidence: 99%
“…Achieving professional identity formation has recently been touted as the new goal to measure competence, as values and attitudes of the professional become incorporated into the identity of the aspiring physician . Faculty trained in such programs could lead institutional initiatives and foster positive change in humanistic professional development at many levels of medical education …”
Section: Discussionmentioning
confidence: 99%
“…The physicians attending the course had been identified by their department heads as being recognized for their humanistic qualities. The course was adapted from a previously described faculty development program at Emory University [ 18 , 19 ]. One member of the research team (NV) conducted semi-structured interviews of 20 to 40 minutes by telephone or in person at the start of the course, using a guide the research team had prepared based on the study objectives and related literature (Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, physicians recognized for their humanistic practice are more likely to experience academic success in medicine and will have improved outcomes as teachers of physicians in training 7 . Published models of faculty development programs for teaching humanism demonstrate that these faculty are more likely to teach humanism in their practice with students and trainees 8,9 . And patients’ experience of provider empathy and compassion can be optimized through educational interventions focused on physicians 10 .…”
Section: Introductionmentioning
confidence: 99%